ANALISIS REVIEW KELENGKAPAN FORMULIR RINGKASAN PULANG DALAM PEMENUHAN ELEMEN PENILAIAN MIRM 15 SNARS EDISI 1 DI RUMAH SAKIT MUHAMMADIYAH SELOGIRI - Mardeni, Febri Sri; Hakam, Fahmi; Asriati, Yul (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2020)
The incompleteness in filling out medical records will greatly affect the SNARS 1stedition accreditation assessment.The results of the assessment from the Hospital AccreditationCommittee survey of the MIRM 15 standard at Muhammadiyah Selogiri Hospital, namely thesummary of going home with the completion level of filling in 2019 has not reached the 100%standard. The purpose of this study was to review the completeness of the return summary form infulfilling the elements of the MIRM 15 SNARS 1st edition assessment at the MuhammadiyahHospital Selogiri. This research used a descriptive research method, with a qualitative approach,the data collection method used observation, interviews, documentation study with the subject of 4officers, the object was all documents of inpatients in February 2020 totaling 571 documents. Thesurvey results revealed the completeness of the summary forms return in February at the reviewsof identification of 100%, review authentication 81%, Review of recording by 64%, reviewsreporting in accordance SNARS element 1 are met incomplete, element 2 is fulfilled complete, theelement 3 is met, the elements 4 are met complete, element 5 is fulfilled completely, element 6 ispartially fulfilled. The conclusion of this study is that the level of completeness of the summaryform home at Muhammadiyah Selogiri Hospital in February 2020 is not according to the standard,namely 11%.